Сompatibility of Actinidia arguta with Schisandra chinensis and Malus domestica plants in mixed plantings - T. B. Venediktova; N.V. Zaimenko; N.V. Skrypchenko (Plant Varieties Studying and Protection)
The accumulation of photosynthetic pigments, biogenic elements and amino acids in the leaves of A. argute (kiwi berry) and S. chinensis (Chinese magnolia vine) during their cultivation in the same vegetative containers was studied. Different ratios of the number of plants in the containers were used, namely 50%:50%, 33%:67%, and 67%:33%. Single-species plantings were used as a control. Research demonstrated that the ratios between co-planted plants can impact the levels of photosynthetic pigments, biogenic elements, and amino acids in their leaves. Mixed planting was found to decrease the concentration of photosynthetic pigments in A. argute leaves under these conditions. The chlorophyll a content showed significant changes, decreasing by 6.7–18.7% with S. chinensis ratio in the container and by 31.3–33.8% with M. domestica ratio compared to mono-planting. Chlorophyll b also showed differences, ranging from 1.2–8.6% and 9.7–29.7%, respectively. Additionally, certain features were observed in the distribution of mineral nutrition elements in plant tissues of A. arguta. In mono-planting conditions, the leaves of plants showed an increase in magnesium, potassium, and phosphorus content. When actinidia is grown together with Chinese magnolia vine and an apple tree, especially with an apple tree, the supply of nitrogen, phosphorus, potassium, and calcium to the plants is sharply reduced. By the end of the growing season of plants, the total content of free amino acids in A. arguta leaves increased in mono-planting conditions. Actinidia plants exhibited a disturbance in phosphate metabolism in mixed plantings, as evidenced by elevated levels of arginine and histidine, as well as altered nitrogen metabolism indicated by decreased concentrations of glutamic acid in the leaves. The competitiveness analysis, using the Vanderbeng and Ennik method, showed that A. arguta plants are more compatible with S. chinensis than with M. domestica. The productivity and sustainability of crops can be significantly increased by using the method of mixed crops in agrophytocenoses. However, it is necessary to consider the bioecological features of plants and their tolerance to root secretions of other species. A. arguta and S. chinensis are forest lianas that are a unique part of forest ecosystems. They grow in multispecies groups in natural conditions, so it can be expected that they will show tolerance in mixed plantings.